Investigation of the preference of marlin Kajikia audax sashimi with different lipid contents through sensory evaluation - Hashimoto, Kanako; Kawashima, Tokifusa; Murata, Yuko; Imamura, Shintaro; Seko, Takuya; Ishihara, Kenji (Frontiers in Sustainable Food Systems, 2024)
Identifying the sensory properties of fish consumers is important for providing their preferred seafood. Odor, flavor, texture, and appearance affected the sensory preference for fish. Moreover, several compounds are involved in sensory preference. This study focused on lipids that affect preference for seafood and examined the lipid content preference in marlin Kajikia audax sashimi. First, lipid contents and fatty acid compositions of different individual sizes and body parts of marlin were compared. Nest, the preference for overall, taste, texture, odor, aftertaste, and lipid content in marlin sashimi taken from different parts of the body with different amounts of lipids was investigated using the paired preference method. Then the relationship of lipid content preference with other preferences were also evaluated using the Chi-square test. The crude lipid of big-sized marlin (51.1-55.1 kg) was 9.5%-13.2%, and the crude lipid of small-sized marlin (23.5-30.0 kg) was 0.8%-1.2%. The dorsal parts of big-sized marlin had lipid contents in the anterior parts higher than those in the posterior parts (p < 0.05). Whereas no differences were observed in the fatty acid composition of different body parts. The lipid content preference for the anterior dorsal part (high lipid part) was higher than that for the posterior dorsal part (lower lipid part) (p < 0.05). However, no difference in overall preference was observed. Additionally, the relationship between lipid content preference and other preference were indicated that the high lipid content parts preferred group significantly preferred the high lipid content parts at overall and taste evaluation (p < 0.01). On the other hand, the low lipid content parts preferred groups showed opposite evaluation. Therefore, the lipid content was associated with the preference for marlin sashimi and be classified into two groups: one prefers high lipid sashimi and the other prefers low lipid sashimi.